Brain imaging abnormalities and outcome after acute ischaemic stroke: the ENCHANTED trial. Issue 12 (14th October 2020) - Delcourt, Candice; Wang, Xia; Zhou, Zien; Wardlaw, Joanna M; Mair, Grant; Robinson, Thompson G; Chen, Xiaoying; Yoshimura, Sohei; Torii-Yoshimura, Takako; Carcel, Cheryl; Calic, Zeljka; Tan, Wee Yong; et al.
Abstract : Objective: To test the hypothesis that imaging signs of 'brain frailty' and acute ischaemia predict clinical outcomes and symptomatic intracranial haemorrhage (sICH) after thrombolysis for acute ischaemic stroke (AIS) in the alteplase dose arm of ENhanced Control of Hypertension ANd Thrombolysis strokE stuDy (ENCHANTED). Methods: Blinded assessors coded baseline images for acute ischaemic signs (presence, extent, swelling and attenuation of acute lesions; and hyperattenuated arteries) and pre-existing changes (atrophy, leucoaraiosis and old ischaemic lesions). Logistic regression models assessed associations between imaging features and death at 7 and 90 days; good recovery (modified Rankin Scale scores 0–2 at 90 days) and sICH. Data are reported with adjusted ORs and 95% CIs. Results: 2916 patients (67±13 years, National Institutes of Health Stroke Scale 8 (5–14)) were included. Visible ischaemic lesions, severe hypoattenuation, large ischaemic lesion, swelling and hyperattenuated arteries were associated with 7-day death (OR (95% CI): 1.52 (1.06 to 2.18); 1.51 (1.01 to 2.18); 2.67 (1.52 to 4.71); 1.49 (1.03 to 2.14) and 2.17 (1.48 to 3.18)) and inversely with good outcome. Severe atrophy was inversely associated with 7-day death (0.52 (0.29 to 0.96)). Atrophy (1.52 (1.08 to 2.15)) and severe leucoaraiosis (1.74 (1.20 to 2.54)) were associated with 90-day death. Hyperattenuated arteries were associated with sICH (1.71 (1.01 to 2.89)). No imaging features modified the effect of alteplase dose. Conclusions: Non-expert-defined brain imaging signs of brain frailty and acute ischaemia contribute to the prognosis of thrombolysis-treated AIS patients for sICH and mortality. However, these imaging features showed no interaction with alteplase dose.